Analisis Semantik Makna Kata Shahib dan Derivasinya dalam Al-Qur’an Juz 29 - Banjarnaor, Riadi; Siregar, Husnatul Hamidiyyah (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This research aims to conduct a semantic analysis of the meaning of the word sh??ib (????) and its derivations in the Qur'an, Juz 29. The background of the study lies in the complexity of meaning (polysemy) in the language of the Qur'an, which necessitates a comprehensive contextual and semantic approach, rather than relying solely on lexical definitions. The word sh??ib, generally meaning